Analyzing glycerol-mediated protein oligomerization by electrospray ionization mass spectrometry - Mendes, M. A.; de Souza, B. M.; dos Santos, L. D.; Santos, K. S.; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2005)
Glycerol is widely used as protein stabilizer, in both local and commercial preparations, so it has become necessary to develop methods for mass spectrometric analysis of protein preparations in the presence of glycerol. However, this stabilizing agent may cause signal suppression when present in high concentrations, and is also known to induce protein supercharging even at low concentrations. This work reports the,use of electrospray ionization (ESI) mass spectrometry to characterize glycerol-mediated protein oligomerization. this phenomenon seems to involve the formation of strong non-covalent interactions between protein and glycerol involving close contact between the monomers, leading to formation of protein oligomers adducted with glycerol molecules under the characteristic analytical conditions of the ESI interface. At high orders of oligomerization a lower number of glycerol molecules is required to maintain the high oligomeric states than for the dimers and trimers, and it is possible that for the higher oligomers the monomers become so close to one another that non-covalent bonds between the side chains of the amino acid residues in the proteins may be established. Copyright (C) 2005 John Wiley & Sons, Ltd.